Validitas dan Reliabilitas Instrumen Sensory Processing Measure 2 (SPM-2) Pada Anak Usia Prasekolah - Arifiati, Retna Febri; Purwati, Diaz (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Developmental milestones are a sequence of skill achievements over time that indicate an interaction of the child's developing nervous system with the environment. Sensory is one aspect of the most important developmental milestones in a child's life and its manifestation in daily life functions in both normal children and children with special needs. Sensory Processing Disorder (SPD) is a condition of neurodevelopmental disorders characterized by difficulty using or organizing sensory information from the body in response to the environment. Sensory Processing Measure-2 or SPM-2 is a measuring tool or instrument that refers to the norms of sensory processing, praxis and social participation in children. The purpose of this study was to determine the results of the SPM-2 home form instrument in preschool children in a valid and reliable manner according to the Indonesian version. Descriptive quantitative research method with cross-section technique. Samples were taken; by random sampling and then conducted validity and reliability tests with the IBM SPSS 26 application. The results of the statistical analysis of the validity test of the SPM-2 home form instrument in preschool children with the Pearson product moment correlation test obtained valid results with a significance value of 0.000 while the SPM-2 reliability test proved reliable, namely each category item showed results at a value greater than >0.600. Conclusion: The SPM-2 home form for preschool children is declared valid and reliable which can be used in Indonesia. The SPM-2 instrument used to measure sensory processing in preschool children and is effective for evaluation for therapists related to sensory disorders in preschool children. This SPM-2 measuring instrument is recommended for further research for children with a diagnosis of Down Syndrome, Hearing loss and other conditions related to sensory processing disorders.